The Effect of First Aid Coaching on First Aid Skills For Dislocations Among High School Students Participating in Sports - Nosi Tamala; Erni Buston; Andra Saferi Wijaya; Septiyanti; Dwi Wulandari (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background of study: Sports injuries, particularly dislocations, are common among sports school students and may lead to serious complications if not treated promptly. However, students first aid knowledge and skills remain limited. This study aimed to determine the effect of First Aid Coaching on first aid skills for dislocations among students at a Sports Talent High School in Bengkulu City. Methods: This study used a quasi-experimental design with a pretest– post-test control group approach. A total of 70 students (n=70) were selected using purposive sampling and divided into an intervention group (n=35) receiving First Aid Coaching and a control group (n=35) receiving leaflets. Data were collected using a knowledge questionnaire and a skills observation sheet and analyzed using the Wilcoxon test and the Independent Samples t-test. Result: The results showed a significant difference in first aid skills between the two groups (p < 0.05). The mean posttest skill score in the intervention group was higher (M = 54.88) compared to the control group (M = 43.06), indicating a greater improvement following First Aid Coaching. Conclusion: In conclusion, First Aid Coaching is more effective than printed media in improving students’ first aid skills for dislocations. This method is recommended as an educational strategy to enhance students’ preparedness in managing sports injuries.